0939 Anxiety Symptoms Moderate the Effects of Sleep Loss on Children's Emotions. (27th May 2020) - Alfano, C A; Bower, J; Harvey, A; Beidel, D; Sharp, C; Palmer, C A
Abstract: Introduction: An abundance of cross-sectional research links inadequate sleep with poor emotional health, but experimental studies in children are rare. Further, the impact of sleep loss is not uniform across individuals, and pre-existing anxiety might potentiate the effects of poor sleep on children's emotional functioning. Methods: N=53 children (mean age 9.0 years; 56% female) completed multi-modal, emotional assessments in the lab when rested and after two nights of sleep restriction (7h and 6h in bed, respectively). Sleep was monitored with polysomnography and actigraphy. Subjective reports of affect and arousal, psychophysiological reactivity, and objective emotional expression were examined during two emotional processing tasks, including one where children were asked to suppress their emotional responses. Results: After sleep restriction, deleterious alterations were observed in children's affect and their emotional reactivity, expression, and regulation. These effects were primarily limited to positive emotional stimuli. The presence of anxiety symptoms moderated most of the alterations in emotional processing observed after sleep restriction. Conclusion: Results suggest inadequate sleep preferentially impacts positive compared to negative emotion in pre-pubertal children and that pre-existing anxiety symptoms amplify these effects. Implications for children's everyday socio-emotional lives and long-term affective risk are highlighted. Support: NIMH grant #R21MH099351